Sebastian Faulks's Genesis Obsession – and Related Issues. (31st October 2018) - Fitzpatrick, Joseph
Abstract: In this article I discuss the surprising similarity between the interpretation of the story told in chapter 3 of Genesis put forward in several of his novels by Sebastian Faulks and my own interpretation set out in my book, The Fall and the Ascent of Man: How Genesis Supports Darwin . 1 Faulks and I argue that Genesis 3 is about hominization, the achievement of human status by a proto‐human couple by the acquisition of self‐awareness. However, that is where the similarity ends. I consider Faulks's understanding of self‐awareness to be seriously mistaken, reductive and incoherent, and I take issue with what I consider to be the consequences of this mistaken understanding.